2012
DOI: 10.1038/emboj.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

The active ClpP protease fromM. tuberculosisis a complex composed of a heptameric ClpP1 and a ClpP2 ring

Abstract: Mycobacterium tuberculosis (Mtb) contains two clpP genes, both of which are essential for viability. We expressed and purified Mtb ClpP1 and ClpP2 separately. Although each formed a tetradecameric structure and was processed, they lacked proteolytic activity. We could, however, reconstitute an active, mixed ClpP1P2 complex after identifying N‐blocked dipeptides that stimulate dramatically (>1000‐fold) ClpP1P2 activity against certain peptides and proteins. These activators function cooperatively to induce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
255
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(266 citation statements)
references
References 66 publications
11
255
0
Order By: Relevance
“…Pioneering work in mycobacteria revealed a heterooligomeric assembly of ClpP1 and ClpP2 in which the interaction of both heptameric rings stimulated activity and exhibited specialized substrate preferences (26). Here we elucidate the high-resolution X-ray structures of LmClpP1, LmClpP1-N172D, as well as LmClpP2 and evaluate their activity by customized probes as well as substrate turnover assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pioneering work in mycobacteria revealed a heterooligomeric assembly of ClpP1 and ClpP2 in which the interaction of both heptameric rings stimulated activity and exhibited specialized substrate preferences (26). Here we elucidate the high-resolution X-ray structures of LmClpP1, LmClpP1-N172D, as well as LmClpP2 and evaluate their activity by customized probes as well as substrate turnover assays.…”
Section: Discussionmentioning
confidence: 99%
“…For a cyanobacterial system, heptameric rings of mixed composition have been reported that interact with different chaperones (22). In contrast, ClpP proteins from L. monocytogenes (LmClpP1 and LmClpP2) as well as from Mycobacterium tuberculosis have been found to assemble into heterooligomeric complexes composed of two homoheptamers (25,26). Inhibition of LmClpP2 with lactonebased inhibitors led to down-regulation of virulence without affecting viability (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S6 A and B). Notably, all peptides known to function as agonists contain an N-terminal carboxybenzyl group (29). The "reverse" binding orientation also explains why agonist peptides are not cleaved, because no peptide bond is positioned for nucleophilic attack by the active-site serine (Fig.…”
Section: Similarities and Differences Between The Clpp1 And Clpp2 Activementioning
confidence: 99%
“…The importance of Clp-family proteolysis in M. tuberculosis is highlighted by the facts that the clpP1, clpP2, clpX, and clpC1 genes are all essential and that mechanism-based ClpP inhibitors suppress growth (24,(26)(27)(28). Recent studies indicate that M. tuberculosis ClpP1 and ClpP2 form discrete heptameric rings that assemble into an active ClpP1P2 tetradecamer only in the presence of a ClpX or ClpC1 AAA+ partner and one additional factor, either protein substrates being actively translocated into the degradation chamber or N-blocked peptide agonists (23,29). Because M. tuberculosis resistance to conventional antibacterial drugs is a major health hazard, there is substantial interest in developing drugs that target ClpP1P2.…”
mentioning
confidence: 99%